2011
DOI: 10.1590/s1415-43662011000900008
|View full text |Cite
|
Sign up to set email alerts
|

Balanço de nutrientes em povoamento de Eucalyptus saligna implantado sobre Cambissolo Háplico no RS

Abstract: A fragilidade de um sistema florestal pode ser avaliada através do balanço de nutrientes, destacando a eficiência da ciclagem sendo que, em certos casos, a adubação deve ser utilizada para manter ou elevar a produtividade do sistema. Objetivou-se com este estudo avaliar o comportamento de diferentes sistemas de preparo de solo em Cambissolo Háplico e sua influência nas perdas de nutrientes transportados por erosão em área cultivada com Eucalyptus saligna. Os tratamentos foram constituídos por quatro métodos de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…One possible explanation for these results is the fact that the residues maintained on soil surface influenced soil water availability (Mendham et al, 2011) and the supply of nutrients by mineralization over time for eucalyptus trees (Hernández et al, 2009;Nambiar & Harwood, 2014;Rocha et al, 2016a). Mazurana et al (2011) found that removal of harvest residues of Eucalyptus grandis presented the greatest loss of nutrients due to soil erosion when compared with their maintenance due to the absence of vegetal material covering the soil surface. Our results are also corroborating with the previous findings of Merino et al (2003), in rainy areas of Northwest Spain, in which the maintenance of harvest residues significantly improved the growth and nutritional status of trees.…”
Section: Influence Of Harvest Residue Management On Tree Growthmentioning
confidence: 99%
“…One possible explanation for these results is the fact that the residues maintained on soil surface influenced soil water availability (Mendham et al, 2011) and the supply of nutrients by mineralization over time for eucalyptus trees (Hernández et al, 2009;Nambiar & Harwood, 2014;Rocha et al, 2016a). Mazurana et al (2011) found that removal of harvest residues of Eucalyptus grandis presented the greatest loss of nutrients due to soil erosion when compared with their maintenance due to the absence of vegetal material covering the soil surface. Our results are also corroborating with the previous findings of Merino et al (2003), in rainy areas of Northwest Spain, in which the maintenance of harvest residues significantly improved the growth and nutritional status of trees.…”
Section: Influence Of Harvest Residue Management On Tree Growthmentioning
confidence: 99%
“…A madeira é um material de grande potencial de uso na construção civil e pode ser procedente de florestas naturais ou plantadas (MAZURANA et al, 2011;MATOS et al, 2012;TER STEEGE et al, 2016;TUISIMA-CORAL et al, 2017). Entre os materiais comumente utilizados, a madeira é o único renovável, expressa elevada relação entre a resistência e o peso, e sua produção gera poucos impactos ambientais.…”
Section: Introductionunclassified
“…Wood is a natural raw material obtained from natural or planted forests (MAZURANA et al, 2011;MATOS et al, 2012;TER STEEGE et al, 2016;TUISIMA-CORAL et al, 2017). In Brazil, Eucalyptus tree genus are utilized for a variety of applications, among them: pulp and paper, charcoal, essential oils, boards, firewood, construction, and furniture (GUIMARÃES JUNIOR et al, 2009BRITO;PERRÉ, 2010;IWAKIRI et al, 2013;SOARES et al, 2015;MATTOS et al, 2014;NEIVA et al, 2015;BALLESTEROS et al, 2015).…”
Section: Introductionmentioning
confidence: 99%